ANALISIS KEMAMPUAN MEMBERIKAN PENJELASAN SEDERHANA DAN MENYIMPULKAN - Tri Epriningsih; Ila Rosilawati; Nina Kadaritna (Universitas Lampung, 2013)
This research aimed to describe the ability to draw conclusions and apply concepts in acid-base material through the application of guided inquiry learning model for high cognitive ability students, medium, and low. The subjects were students of class XI science 2 SMA Negeri 1 Bandar Sribhawono year 2012/2013. This study was pre-experimental research design with one-shot case study. Data analysis used descriptive analysis. Based on the analysis of data it is concluded (1) The ability to apply a case, in high level group just small part were very good, and almost all were good. In intermediate level group, just small part were very good, mostly were good and almost all were enough. In low level group, just small part were very good, half were good, almost all were enough, and just small part were less. (2) ability to drawing conclusions, in high level group almost all were very good and mostly were good. In intermediete level group, almost all were very well, almost all were well, and almost all were enough. In low level group almost all were good and mostly were enough.Kata kunci : kemampuan mengaplikasikan suatu kasus, menarik kesimpulan, kelompok tinggi, sedang, rendah, inkuiri terbimbing